Nurses' experiences of person‐centred care planning using video‐conferencing - Ann‐Therese Hedqvist; Ann Svensson; Lena G. Larsson (Wiley, 2023)
Abstract Aim The aim was to illuminate how nurses experience person‐centred care planning using video conferencing upon hospital discharge of frail older persons. Design Care planning via video conferencing requires collaboration, communication and information transfer between involved parties, both with regard to preparing and conducting meetings. Participation of involved parties is required to achieve a collaborative effort, but the responsibilities and roles of the involved professions are unclear, despite the existence of regulations. Method A qualitative content analysis was conducted based on 11 individual semi‐structured interviews with nurses from hospitals, municipalities and primary care in Sweden. Results This study provides valuable insights into challenges associated with care planning via video conferencing. The meeting format, that is video conferencing, is perceived as a barrier that makes the interaction challenging. Shortcomings in video technology make a person‐centred approach difficult. The person‐centred approach is also difficult for nurses to maintain when the older person or relatives are not involved in the planning.